Predicting Long Term Outcome in Patients Treated With Continuous Flow Left Ventricular Assist Device: The Penn—Columbia Risk Score. Issue 6 (7th March 2018) - Birati, Edo Y.; Hanff, Thomas C.; Maldonado, Dawn; Grandin, E. Wilson; Kennel, Peter J.; Mazurek, Jeremy A.; Vorovich, Esther; Seigerman, Matthew; Howard, Jessica L.L.; Acker, Michael A.; Naka, Yoshifumi; Wald, Joyce; et al.
Abstract : Background: Predicting which patients are unlikely to benefit from continuous flow left ventricular assist device (LVAD) treatment is crucial for the identification of appropriate patients. Previously developed scoring systems are limited to past eras of device or restricted to specific devices. Our objective was to create a risk model for patients treated with continuous flow LVAD based on the preimplant variables. Methods and Results: We performed a retrospective analysis of all patients implanted with a continuous flow LVAD between 2006 and 2014 at the University of Pennsylvania and included a total of 210 patients (male 78%; mean age, 56±15; mean follow‐up, 465±486 days). From all plausible preoperative covariates, we performed univariate Cox regression analysis for covariates affecting the odds of 1‐year survival following implantation ( P <0.2). These variables were included in a multivariable model and dropped if significance rose above P =0.2. From this base model, we performed step‐wise forward and backward selection for other covariates that improved power by minimizing Akaike Information Criteria while maximizing the Harrell Concordance Index. We then used Kaplan–Meier curves, the log‐rank test, and Cox proportional hazard models to assess internal validity of the scoring system and its ability to stratify survival. A final optimized model was identified based on clinical and echocardiographic parameters preceding LVAD implantation. One‐year mortality was significantly higher in patients with higher risk scores (hazard ratio, 1.38; P =0.004). This hazard ratio represents the multiplied risk of death for every increase of 1 point in the risk score. The risk score was validated in a separate patient cohort of 260 patients at Columbia University, which confirmed the prognostic utility of this risk score ( P =0.0237). Conclusion: We present a novel risk score and its validation for prediction of long‐term survival in patients with current types of continuous flow LVAD support.